INTELLECTUAL CAPITAL IN FOCUS: MODULATING CORPORATE GOVERNANCE AND FINANCIAL HEALTH IN NIGERIA’S CONSUMER GOODS SECTOR - Ifeanyi, Samuel Emeka; Adegoke, Grace Chidinma (Research Journal of Economics and Sustainable Development, 2024)
This study examines the relationship between corporate governance and financial performance in Nigeria with a focus on the moderating influence of intellectual capital. Using a sample of consumer goods manufacturing firms from 2011 to 2020, this study investigates the impact of corporate governance mechanisms on the financial performance of listed firms. Four corporate governance mechanisms namely board size, board independence, board compensation, and board meetings were evaluated. A moderating variable, value-added intellectual coefficient (VAIC), was also assessed to determine its impact on the relationship between corporate governance and financial performance. This study uses ex post facto and correlational research designs with a census approach to determine a sample size of 21 firms. Secondary data from the published annual financial reports of the sampled firms was utilized for data analysis. Descriptive statistics, correlation coefficient, and multivariate analysis were employed. The study finds that board independence has a positive and significant relationship with the return on equity of listed consumer goods manufacturing firms in Nigeria, while board compensation has a negative and significant effect on return on equity. Additionally, board diligence has a positive and significant relationship with return on equity, and intellectual capital positively and significantly moderates the relationship between corporate governance mechanisms and return on assets. The study concludes that intellectual capital moderates the relationship between corporate governance attributes and the financial performance of listed consumer goods manufacturing firms in Nigeria. Therefore, policymakers should emphasize good corporate governance practices with quality intellectual input as a means of improving the level of financial performance.